Effects of yoga training in patients with chronic obstructive pulmonary disease: a systematic review and meta-analysis - Liu, Xun-Chao; Pan, Lei; Hu, Qing; Dong, Wei-Ping; Yan, Jun-Hong; Dong, Liang (Journal of Thoracic Disease; Vol 6, No 6 (June 26, 2014): Journal of Thoracic Disease, 2014)
Introduction: Currently, several studies have assessed the effect of yoga training on the management of chronic obstructive pulmonary disease (COPD), but these studies involved a wide variation of sample and convey inconclusive results. Hence, the present study was performed a systematic review and meta-analysis to investigate the efficacy of yoga training in COPD patients. Methods: PubMed, EMBASE, the Cochrane Library, Google Scholar, and ClinicalTrials.gov databases were searched for relevant studies. The primary outcomes were forced expiratory volume in one second (FEV1), FEV1% predicted (% pred). Secondary outcomes included 6-min walking distance (6 MWD), arterial oxygen tension (PaO2), and arterial carbon dioxide tension (PaCO2). Weighted mean differences (WMDs) and 95% confidence intervals (CIs) were calculated, and heterogeneity was assessed with the I2 test. Results: Five randomized controlled trials (RCTs) involving 233 patients fulfilled the inclusion criteria. Yoga training significantly improved FEV1 (WMD: 123.57 mL, 95% CI: 4.12-243, P=0.04), FEV1% pred (WMD: 3.90%, 95% CI: 2.27-5.54, P